Trial of an associated surgical and biological treatment in cancer of the digestive system - Badano Repetto, Jose; Acosta Andreotti, Juan; Badano Carbajal, Jose; Costa Roel, Julio; Lopez Susviela, Juan (Cirugía del Uruguay, 1971)
The authors present a combined surgical and biological treatment of cancers of the. digestive system. Cancerous disease is defined as "inmuno paresia" with focal manifestations. The properties of "Selye's inmunitary granuloma", adapted to clinical application and cancerous disease, are. used to produce a rejection phenomen in the tumor. Reintroduction of the neoplasic ascites liquid is associated with an operation created by the . authors. According to the working nypothesis, the authors disagree. with ultra-radical surgery and the use of radiation or citostatic drugs acting as inmuno-depressors.